Biomass-modulated fire dynamics during the last glacial-interglacial transition at the Central Pyrenees (Spain) (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
Understanding long-term fire ecology is essential for current day interpretation of ecosystem fire responses. However palaeoecology of fire is still poorly understood, especially at high-altitude mountain environments, despite the fact that these are fire-sensitive ecosystems and their resilience might be affected by changing fire regimes. We reconstruct wildfire occurrence since the Lateglacial (14.7calka BP) to the Mid-Holocene (6calka BP) and investigate the climate–fuel–fire relationships in a sedimentary sequence located at the treeline in the Central Spanish Pyrenees. Pollen, macro- and micro-charcoal were analysed for the identification of fire events (FE) in order to detect vegetation post-fire response and to define biomass–fire interactions. mean fire intervals (mfi) reduced since the Lateglacial, peaking at 9–7.7calka BP while from 7.7 to 6calka BP no fire is recorded. We hypothesise that Early Holocene maximum summer insolation, as climate forcing, and mesophyte forest expansion, as a fuel-creating factor, were responsible for accelerating fire occurrence in the Central Pyrenees treeline. We also found that fire had long-lasting negative effects on most of the treeline plant communities and that forest contraction from 7.7calka BP is likely linked to the ecosystem's threshold response to high fire frequencies.

Environmental implications of pollen spectra in bat droppings from southeastern Spain and potential for palaeoenvironmental reconstructions (Review of Palaeobotany and Palynology, 2006)
Pollen was analysed from bat guano from nine caves in southeastern Spain and surface soils in their immediate surroundings. We compare the pollen spectra of 34 modern dung samples from the nine caves with one modern surface pollen sample from each cave. The contents suggest reasonable pollen diversity and richness, including anemophilous and zoophilous pollen types. Since the latter is usually under-represented in atmospheric pollen, the guano spectra therefore appear to reflect the vegetation more effectively than normal surface soil samples. Despite health hazards such as histoplasmosis, the difficulties of obtaining bat guano in deep caves and possible interpretational concerns relating to behaviour and feeding habits of different bat species, this material can be very useful in palaeoecological research provided that the dung was fossilized under favourable environmental conditions that allowed the preservation of pollen.